Sub-Saharan Africa : Building Resilience to Climate-Related Disasters - Pondi Endengle, Eric M. (IMF Working Papers; Working Paper ;, 2022)
This paper assesses the impact of climate-related disasters on medium-term growth and analyzes key structural areas that could substantially improve disaster-resilience. Results show that (i) climaterelated disasters have a significant negative impact on medium-term growth, especially for sub-Saharan Africa; and (ii) a disaster's intensity matters much more than its frequency, given the non-linear cumulative effects of disasters. In sub-Saharan Africa, electrification (facilitating irrigation) is found to be most effective for reducing damage from droughts while improved health care and education outcomes are critical for raising resilience to floods and storms. Better access to finance, telecommunications, and use of machines in agriculture also have a significant impact.